Automated patient-specific clavicle reconstruction plate design process - De Wet, Charl (Stellenbosch : Stellenbosch University, 2025)
de Wet, C. 2025.Automated Patient-Specific Clavicle Reconstruction Plate Design Process. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/37b3b0bd-2b18-4e20-a925-b519e6bbf880